PERANCANGAN SISTEM INFORMASI AKUNTANSI STANDAR SATUAN HARGA BARANG DI PEMERINTAH KOTA CIMAHI - Oktavia, Erni; Hernawati, Euis; Kusumadiarti, Rini Suwartika (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This research was conducted to analyze and design a standard unit price informationsystem at the Regional Financial and Asset Management Agency (BPKAD) of the CimahiCity Government in order to simplify and streamline the time for preparing unit pricestandards as an important component of the RKA-SKPD. The problem factor found is thatthe process of recording important data related to the preparation of unit price standards iscarried out in a semi-computerized manner using Microsoft Excel, this poses a large risk ofdata loss and lacks effectiveness in managing important data. Therefore, it is necessary toupdate the data recording system that can support the preparation of the SSH compilationteam. The research method used is a qualitative research method with a descriptiveapproach. Data collection techniques include field work practices, interviews with thedrafting team, and literature studies sourced from books, internet, and journals with similarscope. The system design method uses the Waterfall method or Linear Sequential Modelwhich is applied to the PHP and MySQL programming languages as databases. With theresulting information system, it is hoped that it can support the needs of the drafting teamin the preparation of unit price standards and database updates for important datasecurity.